Cell-surface Proteoglycan Expression by Lymphocytes from Peripheral Blood and Gingiva in Health and Periodontal Disease - Manakil, J.F.; Sugerman, P.B.; Li, H.; Seymour, G.J.; Bartold, P.M. (Journal of dental research, 2001)
Cell-surface proteoglycans are involved in lymphocyte migration and activation. This study investigated the expression of syndecan-1, syndecan-4, and glypican in peripheral blood lymphocytes and by lymphocytes in variously inflamed periodontal tissues. Gingival specimens from healthy, gingivitis, or chronic periodontitis sites were stained by means of antibodies against B- and T-lymphocytes and also syndecan-1, syndecan-4, and glypican. Syndecan-1 expression by peripheral blood mononuclear cells (PBMC) from healthy, gingivitis, and chronic periodontitis subjects was assessed by flow cytometry. Syndecan-1 was expressed by B-cells/plasma cells but not T-cells in both gingivitis and chronic periodontitis lesions. Both B-cells/plasma cells and T-cells in gingivitis and chronic periodontitis expressed syndecan-4. Glypican was expressed only by macrophages. Stimulation of PBMC with mitogens and growth factors modulated syndecan-1 expression in both the T- and B-cells. Thus, cell-surface proteoglycan expression by lymphocytes in periodontal inflammation is cell-type-specific and may be modulated by inflammation.